From Mental Health to Mental Wealth in Athletes: Looking Back and Moving Forward - Uphill, Mark; Sly, Dan; Swain, Jon (Frontiers in Psychology, 2016)
Considerations of athletes’ mental health are typically framed in the language of mental illness (Hughes and Leavey, 2012), a situation that contributes to stigmatization, denial, and the prevention of effective care. In this article, we provide a critical, narrative review of the extant literature on athlete mental health. Specifically, we begin by providing a brief synopsis of the extant literature on athletes’ mental health, illustrating both what we know about (i) the prevalence of mental health issues in sport and (ii) variables contributing to help-seeking behaviors in athletes. Against, this backdrop, we outline Keyes’ (2002) two-continuum model of mental health as a theoretical framework that has considerable promise in understanding, talking-about, and intervening to enhance, athletes’ mental health. This model posits two related, but distinct dimensions: one continuum indicates the presence or absence of mental health, the other the presence or absence of mental illness. From this perspective, a number of possibilities emerge. For instance, athletes could simultaneously have both positive mental health and experience of mental illness. Alternatively, athletes could be free from mental illness, but in Keyes’ terms be “languishing” (i.e., experiencing low levels of mental health). Implications for interventions based on the two-continuum model are discussed, particularly drawing on assets-based approaches to enhance flourishing (Theokas et al., 2005). We conclude the review by considering limitations in our understanding of how to promote flourishing and suggest avenues for further research.